Variations in Pesticide Doses under Field Conditions - Velini, E. D. [UNESP] (2017)
Univ Estadual Paulista Julio de Mesquita Filho UN, Coll Agr Sci, Fac Ciencias Agron, Dept Crop Sci,Sao Paulo State Univ, Rua Dr Jose Barbosa de Barros 1780, BR-18610307 Botucatu, SP, Brazil